A Conceptual Model for Sustainable Network Expansion to Reach Economically Disadvantaged Communities - Nasiru Hayatu; Abraham Ayodeji Abayomi; Abel Chukwuemeke Uzoka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Expanding network infrastructure to economically disadvantaged communities is essential for promoting digital inclusion, economic empowerment, and equitable access to essential services. This paper proposes a conceptual model for sustainable network expansion that addresses the unique financial, technical, and socio-political challenges associated with connecting underserved populations. The model integrates strategic planning, community engagement, and innovative technology deployment to ensure both affordability and long-term viability. The framework emphasizes the use of low-cost, energy-efficient technologies such as small cell networks, community-based wireless mesh systems, and solar-powered base stations to minimize capital and operational expenditures. By leveraging renewable energy and scalable architectures, the model supports sustainable growth in areas with limited infrastructure. Furthermore, the integration of public-private partnerships and community ownership models ensures local participation, boosts digital literacy, and fosters a sense of shared responsibility. A critical component of the model is a data-driven site selection mechanism that utilizes geospatial analysis and demand forecasting to prioritize deployment in regions with high socio-economic need and low connectivity. The paper also outlines policy recommendations for universal service obligations, spectrum allocation, and fiscal incentives to encourage investment in marginalized regions. By aligning network expansion strategies with national development goals and Sustainable Development Goals (SDGs), the model provides a roadmap for inclusive digital transformation. Through comparative case studies, the paper demonstrates how similar frameworks have succeeded in various global contexts, including sub-Saharan Africa, South Asia, and Latin America. These examples highlight the potential socio-economic impacts of improved connectivity, such as increased access to education, telehealth, financial services, and entrepreneurship opportunities. In conclusion, the proposed conceptual model offers a holistic and replicable approach to bridging the digital divide in economically disadvantaged communities. It advocates for innovation, inclusivity, and sustainability as the foundation for meaningful and impactful network expansion that aligns with both social equity and economic development imperatives.